Keloid disorder: Fibroblast differentiation and gene expression profile in fibrotic skin diseases. Issue 1 (20th December 2020) - Macarak, Edward J.; Wermuth, Peter J.; Rosenbloom, Joel; Uitto, Jouni
Abstract: Keloid disorder, a group of fibroproliferative skin diseases, is characterized by unremitting accumulation of the extracellular matrix (ECM) of connective tissue, primarily collagen, to develop cutaneous tumors on the predilection sites of skin. There is a strong genetic predisposition for keloid formation, and individuals of African and Asian ancestry are particularly prone. The principal cell type responsible for ECM accumulation is the myofibroblast derived from quiescent resident skin fibroblasts either through trans ‐differentiation or from keloid progenitor stem cells with capacity for multi‐lineage differentiation and self‐renewal. The biosynthetic pathways leading to ECM accumulation are activated by several cytokines, but particularly by TGF‐β signalling. The mechanical properties of the cellular microenvironment also play a critical role in the cell's response to TGF‐β, as demonstrated by culturing of fibroblasts derived from keloids and control skin on substrata with different degrees of stiffness. These studies also demonstrated that culturing of fibroblasts on tissue culture plastic in vitro does not reflect their biosynthetic capacity in vivo. Collectively, our current understanding of the pathogenesis of keloids suggests a complex network of interacting cellular, molecular and mechanical factors, with distinct pathways leading to myofibroblast differentiation and activation. Keloids can serve as a model system of fibrotic diseases, a group of currently intractable disorders, and deciphering of the critical pathogenetic steps leading to ECM accumulation is expected to identify targets for pharmacologic intervention, not only for keloids but also for a number of other, both genetic and acquired, fibrotic diseases.